2021
DOI: 10.1097/ta.0000000000003366
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot wounds sustained during legal intervention versus those inflicted by civilians: A comparative analysis

Abstract: BACKGROUND:Existing data demonstrate that injuries sustained during legal intervention (LI) differ from those incurred during civilian interpersonal violence (CIV), but gunshot wounds (GSWs) have not yet been specifically examined. This study was undertaken to provide an in-depth analysis of patients shot during LI versus CIV. METHODS:Patients injured by GSW and captured by the National Trauma Data Bank (2007-2017) were included. Exclusions were transfer from outside hospital or self-inflicted, accidental, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…As corroborated by Schellenberg et al, increased resource use may be driven by greater requirement for emergency operations and increased need for ICU admission. 3 Due to the higher odds of cardiac complications and respiratory failure, management of these complications may also be contributors to increased costs. Finally, although need for major operations was similar, ISs were found to have a greater requirement of head and truncal operations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As corroborated by Schellenberg et al, increased resource use may be driven by greater requirement for emergency operations and increased need for ICU admission. 3 Due to the higher odds of cardiac complications and respiratory failure, management of these complications may also be contributors to increased costs. Finally, although need for major operations was similar, ISs were found to have a greater requirement of head and truncal operations.…”
Section: Discussionmentioning
confidence: 99%
“…2 Additionally, Schellenberg and colleagues found that compared to civilian firearm injuries, those injured during LEI were more likely to have higher ISS, increased need for emergent surgical interventions, and greater mortality. 3 Collectively, these findings highlight the significant morbidity of patients injured after LEI.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations